Perancangan hunian dengan pendekatan arsitektur bioklimatik untuk mencapai kenyamanan termal - Ningsih, Fitria (Maliki Interdisciplinary Journal, 2024)
There are many architectural approaches that have developed among experts, one of which is Bioclimatic Architecture. Bioclimatic was born in the mid-20th century as a solution to design problems in the context of climate. This article discusses the application of the Bioclimatic Architecture concept in order to adapt to the climate to create thermal comfort, especially to the tropical climate in Malang City. The design object that the author focuses on is a residential house. Some of the variables that become the principles of the Bioclimatic Architecture approach are building orientation, wall design, use of transition spaces, landscape processing, and the use of passive shading. All of these variables have an important role in designing residential houses that are adaptive and solutive to thermal issues due to climate conditions.